PENGARUH PROGRAM PEREGANGAN TERSTRUKTUR TERHADAP PENINGKATAN FLEKSIBILITAS OTOT DAN EFISIENSI TEKNIK RENANG GAYA KUPU-KUPU - Natasya Sormin; Naufal Hatta; Alfonso Siahaan; Nurhayati Simatupang (STKIP Subang, 2026)
Butterfly stroke is one of the most physically demanding swimming styles, requiring exceptional upper-body flexibility and core coordination. Without adequate range of motion in the shoulders, back, and ankles, swimmers experience decreased propulsion and an increased risk of injury. This study aims to investigate the effect of a targeted stretching program on improving muscle flexibility and technical efficiency in butterfly stroke swimming. The methodology employed a quantitative approach with a pretest-posttest control group design involving 50 student-athletes divided equally into an experimental group and a control group. The experimental group underwent a structured 6-week stretching regimen focusing on the pectoralis, deltoids, latissimus dorsi, and ankle joints, while the control group maintained their regular routine. Data were collected using goniometric measurements for shoulder flexibility and video analysis for stroke efficiency. The results indicated a significant increase in shoulder flexibility within the experimental group, with pretest and posttest scores rising from 36 to 61. Furthermore, enhanced ankle flexibility led to a more powerful dolphin kick and a more streamlined body position. In conclusion, integrating a specialized stretching program into regular training routines substantially enhances technical performance and reduces flexibility-related limitations in butterfly stroke swimmers. It is recommended for future research to analyze the direct correlation between ankle flexibility and underwater dolphin kick velocity.